The Impact of Pay and Workplace Conditions on Employee Performance with Job Satisfaction Acting as an Intermediary - Yudika, Rifky Setiya; Zain, Efendy (Human Capital and Organizations, 2025)
This study uses job happiness as an intervening variable to examine how pay and work environment affect employee performance. This investigation was carried out at the social security organization BPJS Ketenagakerjaan Cilincing Branch. Thirty BPJS Ketenagakerjaan Cilincing Branch employees made up the study's population. The research methodology is quantitative, and questionnaires are utilized to collect data distributed to all employees as research samples. The saturation sampling approach is the method employed in the sampling process. The WarpPls Partial Least Square Structural Equation Modeling (PLS-SEM) approach is the data analysis technique employed. The study's findings indicate that remuneration does not affect employee performance; work environment has an impact on employee performance; compensation does not affect job satisfaction; work environment has an impact on job satisfaction; compensation does not affect employee performance through job satisfaction as an intervening variable; and job satisfaction influences employee performance. The managerial consequence is that regular surveys and evaluations are crucial for understanding the needs of employees and expectations. In this way, companies can identify areas that need improvement and adjust existing policies.